Politics in the Works of Al-Ghazzālī - Kamaruddin, Rusli (Intellectual Discourse, 2004)
Al-Ghazzālī was a theologian and a prolific writer. Even though he wrote mainly on doctrines, there are many passages in his wide ranging works which treat politics. Indeed, there are certain treatises that are exclusively devoted to topics studied in political science. The four works analyzed here show that he was, among other things, a political thinker whose aim was to synthesize politics with Islam. He discussed extensively the concepts of imāmah and khilāfah detailing its prerequisites and the qualifications required of the office holders. Any attempts at understanding political thought of al-Ghazzālī must adopt a comprehensive approach by looking at all of his works and by situating the works within the specific context in which these were written.